Meningkatkan Sikap Positif Terhadap Perilaku Tidak Merokok dan Kecenderungan untuk Berhenti Merokok Melalui Pelatihan - T. Cut Lizam, Yayi Suryo Prabandari, Amitya Kumara (Berita Kedokteran Masyarakat (BKM), 2009)
Background: Almost  everybody knows  that  smoke could  endangered smoker’s  health  and  people  surrounding (passive  smoker). The  influence  of  peer, self  appearance,  curiosity,  stress, boring, masculinity and  rebelience are some of major  issues  that could contribute  teenagers  to start smoking. Therefore, health education  is needed to  improve positive  attitude  toward  non smoking  behavior and  tendency  to  quit  smoking  by empowering  their own  emotional  through  emotional  intelligence  training.Objective: This  research was  aimed  to  find out  the  influence  of  training on  emotional  intelligence  in  order  to improve  positive attitude  toward non  smoking behavior  and  tendency  to quit  smoking  in  intervention  group  and the difference  on attitude  as well  as  intention  to quit  smoking  in  intervention group with control  group.Method: Quasi  experimental study was conducted with pre-test  and  post-test with  control design. Experiment group was  given  training  on  emotional  intelligence with  lecture method  and  sensitivity  training. The  research subjects were 43  in  intervention  group  and  41  in  control  group with  research  population was  boys who  smoke in  grade  II of  social science majoring  class. Data  analysis was conducted with  paired  t-test  for  one group  and independent  t-test  in  different  group with  significance  level of  5% or  p<0.05.Result: There was a  significant  positive  improvement  on  attitude  toward  non  smoking  behavior  especially  in pretest and  posttest-1, pretest  and  posttest  2  (p<0.05)  and  there was  an  improvement  on  tendency  to  quit smoking  in  intervention group. There was  a significant  difference  (p<0.05)  on attitude  in  intervention and  control groups. Furthermore,  there was  not  an  improvement  on  positive  attitude  toward  non  smoking  behavior  in intervention  group  especially  in  the  indicator of  self motivation  and  in  posttest 1  and posttest  2.Conclusion: Health  education  through  training  on  emotional  intelligence  could  improve  positive attitude  toward non  smoking  behavior  and  tendency  to quit  smoking  in  teenager.Keywords:  training  on emotional  intelligence, attitude  toward smoking  and  tendency  to quit  smoking